Role of MoOx Surficial Modification in Enhancing the OER Performance of Ru–Pyrochlore. Issue 10 (15th January 2023) - Liu, Tongtong; Guo, Hengyu; Chen, Yanan; Zhang, Zhengping; Wang, Feng
Abstract: Pyrochlore ruthenate (Y2 Ru2 O7–δ ) is highlighted as a promising oxygen evolution reaction (OER) catalyst for water splitting in polymer electrolyte membrane electrolyzers. However, an efficient electronic modulation strategy for Y2 Ru2 O7–δ is required to overcome its electrochemical inertness. Herein, a surface manipulation strategy involving implanting MoOx moieties on nano Y2 Ru2 O7–δ (Mo–YRO) using wet chemical peroxone method is demonstrated. In contrast to electronic structure regulation by intramolecular charge transfer (i.e., substitutional strategies), the heterogeneous Mo−O−Ru micro‐interfaces facilitate efficient intermolecular electron transfer from [RuO6 ] to MoOx . This eliminates the bandgap by inducing Ru 4 d delocalization and band alignment rearrangement. The MoOx modifiers also alleviate distortion of [RuO6 ] by shortening Ru−O bond and enlarging Ru−O−Ru bond angle. This electronic and geometric structure tailoring enhances the OER performance, showing a small overpotential of 240 mV at 10 mA cm −2 . Moreover, the electron‐accepting MoOx moieties provide more electronegative surfaces, which serve as a protective "fence" to inhibit the dissolution of metal ions, thereby stabilizing the electrochemical activity. This study offers fresh insights into the design of new‐based pyrochlore electrocatalysts, and also highlights the versatility of surface engineering as a way of optimizing electronic structure and catalytic performance of other related materials. Abstract : Heterogeneous micro‐ Mo−O−Ru interfaces are constructed by implanting MoOx moieties on nano Y2 Ru2 O7 . The MoOx modifiers alter the geometric surface structure of Y2 Ru2 O7, alleviating the distortion of [RuO6 ] centers. Intermolecular electron transfer from [RuO6 ] to MoOx modifies the electronic structure of [RuO6 ]. The electron‐accepting MoOx moieties serve as an electronegative "fence", which stabilizes Y2 Ru2 O7 by efficiently inhibiting the dissolution of metal ions.